POULTRY PRODUCTION AND SELLING CLASSIFICATIONS IN JIMMA HORRO WEREDA, OROMIA WESTERN WOLLEGA - Abdisa, Soresa Shuma; Challa, Abdisa Abraham; Bedane, Moti Erena (International Journal of Research -GRANTHAALAYAH, 2021)
A survey was conducted at Jimma Horro District, Oromia Region. The key purpose of the study was to describe the present poultry production and selling structure of the Jimma Horro District. Over-all 165 aimlessly nominated poultry holders were used for the study. As the results, indicate there were three poultry manufacture structures in the study areas, foraging with seasonal feed supplementation (86.7%). The mean amount of eggs placed/clutch and yearly yield of local hens was 12.3 and 39.8eggs respectively. There was no formal chicken and chicken product marketing channel in the Jimma Horro District and informal marketing of live birds and eggs involving open markets are common throughout the district.